Investigating influence of streetscape elements on individual preference - Liu, Yue (Rebecca) (Kansas State University, 2015)
Streets and sidewalks are important public places for a wide variety of activities, such as social interaction and physical activities. Public spaces can provide numerous benefits, such as physical, psychological, social, spiritual, and aesthetic wellbeing; in order to maximize these benefits effective planning and design is critical. However, there is a need to increase empirical data which can support good planning for these public spaces. The purpose of this research study is to better understand how different elements of streetscape design influence a person’s preferences for the design of the space. A streetscape consists of a variety of different infrastructure and natural forms, which are combined together to create a space centered on the movement of people. A survey was conducted with the aims to better understand how key design elements may influence users’ preferences with regard to safety and attractiveness. The project study site is Moro Street in Aggieville Business District in Manhattan, KS. The study and survey were developed using the psychophysical approach, which employed a quantitative methods to analyze the perceptions of Aggieville patrons. The research methods consists of four main parts: variable selection, streetscape design, public survey, and data analysis. An ANOVA was conducted that revealed statistically significant effects related to the preference for streetscape design in terms of safety and attractiveness, as well as a combined average evaluation. Evidence shows that the on street parking (Parking) and green infrastructure (Green Infrastructure) are statistically significant (p < .05), whereas seating and biking had no statistically significant effect on the evaluation of attractiveness. Also, the on street parking (Parking), green infrastructure (Green Infrastructure) and bike lane (biking)are statistically significant (p < .05), whereas seating had no statistically significant effect on the evaluation of safety. Overall, on street parking (Parking) and green infrastructure (Green Infrastructure) are statistically significant (p < .05), whereas seating and biking had no statistically significant effect on the evaluation of both safety and attractiveness. These results support previous work from environmental psychologists, and provide additional empirical evidence to support effective street design.
Keywords: Psychophysical approach; Streescape elements; Pedestrian-friendly street design; ANOVA; Landscape Architecture (0390)